2002
DOI: 10.1165/rcmb.2002-0048oc
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction and Remodeling of the Mouse Airway Persist after Resolution of Acute Allergen-Induced Airway Inflammation

Abstract: The mechanisms underlying airway hyperresponsiveness remain unclear, although airway inflammation and remodeling are likely important contributing factors. We hypothesized that airway physiology would differ between mice subjected to brief or chronic allergen exposure, and that these differences would be associated with characteristic inflammatory markers and indices of airway remodeling. BALB/c mice were sensitized to ovalbumin and studied at several time points following brief or chronic allergen challenge p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
192
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(215 citation statements)
references
References 43 publications
20
192
3
Order By: Relevance
“…Perhaps, after initiation of the remodeling process, which collectively requires CD4 T cells, other CD4ϩ cells, and eosinophilic inflammation, a number of growth factors and cytokines, including TGF-␤1 and VEGF, produced by CD4-negative cell types such as macrophages or activated epithelial cells, are sufficient for maintenance of remodeling as implied from other reports (25,31). Although our data support an uncoupling of inflammation and remodeling similar to prior observations (13,20,27,31), the mechanisms that lead to such a divergence have yet to be fully elucidated.…”
Section: Discussionsupporting
confidence: 87%
“…Perhaps, after initiation of the remodeling process, which collectively requires CD4 T cells, other CD4ϩ cells, and eosinophilic inflammation, a number of growth factors and cytokines, including TGF-␤1 and VEGF, produced by CD4-negative cell types such as macrophages or activated epithelial cells, are sufficient for maintenance of remodeling as implied from other reports (25,31). Although our data support an uncoupling of inflammation and remodeling similar to prior observations (13,20,27,31), the mechanisms that lead to such a divergence have yet to be fully elucidated.…”
Section: Discussionsupporting
confidence: 87%
“…Ovalbumin Sensitization/Challenge Model and Isolation of Murine Airway Smooth Muscle Cells-BALB/c mice (Charles River Laboratories, Wilmington, MA) were sensitized and challenged to endotoxin-free ovalbumin (Pierce), as previously described (30). On day 0, mice were anesthetized and injected intraperitoneally with 200 l of a suspension of 25% (w/v) alum (Pierce) in either PBS or ovalbumin (5 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms by which each exacerbates the other, or whether a direct connection exists between the two, remain highly debated. Although it is suggested that airway inflammation precedes the development of both pathologies (9,10), airway structural alterations may also independently modify AHR (11,12). It is suggested that frequent asthma exacerbations evoke an airway injury-repair cycle that promotes sustained AHR by altering the structure and function of ASM cells (13,14).…”
Section: Airway Remodeling and Ahr: A Direct Relation?mentioning
confidence: 99%